2011
DOI: 10.1016/j.ijrobp.2011.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Use of Implanted Markers and Interportal Adjustment With Real-Time Tracking Radiotherapy System to Reduce Intrafraction Prostate Motion

Abstract: Purpose: Interportal adjustment was applied to patients with prostate cancer using three fiducial markers and two sets of fluoroscopy in a real-time tumor-tracking radiotherapy (RTRT) system. The incidence of table position adjustment required to keep intrafractional uncertainty within 2.0 mm was investigated in this study. Methods and Materials:The coordinates of the center of gravity of the three fiducial markers were measured at the start of every portal irradiation in intensity-modulated radiotherapy (IMRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…Simulation setup Figure 1 shows the water phantom geometry, coordinate system, and beam directions. The phantom size (38× 20×20 cm 3 ) was determined based on the average anatomical measurements of water equivalent length made from computed tomography scans of 10 prostate cancer patients' pelvises. Clinical target volume (CTV) was defined as prostate and its size ranges from 28 to 74 cm 3 (44 cm 3 on average) over the 10 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation setup Figure 1 shows the water phantom geometry, coordinate system, and beam directions. The phantom size (38× 20×20 cm 3 ) was determined based on the average anatomical measurements of water equivalent length made from computed tomography scans of 10 prostate cancer patients' pelvises. Clinical target volume (CTV) was defined as prostate and its size ranges from 28 to 74 cm 3 (44 cm 3 on average) over the 10 patients.…”
Section: Methodsmentioning
confidence: 99%
“…During irradiation, continuous target tracking by a fluoroscopic X-ray system is useful for respiratory moving tumors 1 . It has been reported that even the prostate can undergo more than 10 mm of intra-fractional motion during 1 minute 2 , which suggests that real-time tracking is also beneficial for the prostate 3 . Due to their high opacity, gold markers have been used with great effect especially for the cases of liver and prostate with the targets surrounded by water-equivalent tissues.…”
Section: Introductionmentioning
confidence: 99%
“…We have also found that a method using multiple gold markers with frequent correction of the table position during RT is useful to reduce the error due to intrafractional organ motion (24). We inserted more than three markers around the tumor bed to be covered in the image-guided boost in principle, since the bladder wall is so flexible.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are asked to void a few hours before every radiotherapy. The details of this procedure were as reported [6,8]. …”
Section: Methodsmentioning
confidence: 99%
“…This system can maintain accuracy within nearly 2 mm during radiotherapy by reducing the intra-fractional as well as inter-fractional errors, and it could also be called on-line image-guided radiotherapy with intra-fractional correction (intra-IGRT) [6]. We have not yet encountered any situation in which the precision of intra-IGRT would be required rather than non-intra-IGRT technologies that do not improve intra-fractional accuracy but do improve inter-fractional accuracy (inter-IGRT).…”
Section: Introductionmentioning
confidence: 99%